2014
DOI: 10.1158/1055-9965.epi-13-0965
|View full text |Cite
|
Sign up to set email alerts
|

Association between Allergies and Risk of Pancreatic Cancer

Abstract: Background Less than 10% of pancreatic cancer cases survive five years, yet its etiology is not well understood. Studies suggest allergies are associated with reduced pancreatic cancer risk. Our study collected additional information on allergies (including skin prick test results and differentiation of allergic/non-allergic asthma), and is the first to assess possible confounding by allergy medications. Methods A population-based case-control study was designed to comprehensively assess the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 73 publications
4
53
0
1
Order By: Relevance
“…If cases come from a defined group such as members of a health maintenance organization, controls without the disease of interest are generally sampled from among other members of the defined group. Cotterchio et al (2014) used a case-control design to evaluate a possible protective effect of allergies against the development of pancreatic cancer. The study included 345 newly diagnosed pancreatic cancer cases during 2011 and 2012 identified from the Ontario Cancer Registry, which collects data on all cancer cases diagnosed in the Province of Ontario, Canada.…”
Section: Case-control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If cases come from a defined group such as members of a health maintenance organization, controls without the disease of interest are generally sampled from among other members of the defined group. Cotterchio et al (2014) used a case-control design to evaluate a possible protective effect of allergies against the development of pancreatic cancer. The study included 345 newly diagnosed pancreatic cancer cases during 2011 and 2012 identified from the Ontario Cancer Registry, which collects data on all cancer cases diagnosed in the Province of Ontario, Canada.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Protective associations were observed for hay fever, dust or mold allergies, and animal or pet allergies, consistent with prior studies, but not for food or medication allergies or allergic asthma. In contrast to the approach of Cotterchio et al, 2014, Amadou et al, 2014 recruited women with newly diagnosed cases of breast cancer from 12 hospitals at the major health care institutions in three large regions in Mexico, and sampled controls from the same five-year age group, the same region and with membership in the same health care institution as the cases. They used this type of case-control approach to determine the association between anthropometric characteristics and breast cancer in Mexico.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…[5][6][7][8][9] Over the past few decades, substantial amounts of epidemiologic and clinical data have described the associations between allergic diseases and cancer. [5][6][7][8][9][10][11][12] However, to the best of our knowledge, only a few epidemiologic studies have examined the associations between allergic diseases and gastric cancer. One cohort study that analyzed subjects selected from a hospital discharge registry, reported that asthma was associated with reduced gastric cancer risk; 13 however, this study included patients with only severe asthma, and the number of gastric cancer cases was small.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports have largely replicated the inverse association between PDAC and nasal allergies with only one study reporting a non-significant reduced estimate 21–25. Regarding skin allergies, two additional articles reported reduced estimates but only one showed statistical significance 24 25. Conversely, the association between asthma and PDAC risk has remained inconclusive.…”
Section: Introductionmentioning
confidence: 99%